Immunological Correlates of the Vitamin D–ALP Axis in Pediatric Patients (Ages 1–5 Years) Non Hospitalized with Type 1 Diabetes Mellitus - Jomah, Ashraf Fadhil (American Journal of Biology and Natural Sciences, 2025)
Recently, vitamin D deficiency which have been associated with the pathogenesis of T1DM has received closer attention, especially in young children and where immune dysregulation is more prominent. The objective of this study was to investigate serum 25-hydroxyvitamin D [25(OH)D] levels and association with immunological markers in T1DM non hospitalized children aged 1–5 years. Serum 25(OH)D, alkaline phosphatase (ALP), immunoglobulins (IgG, IgM and IgA), and diabetes-associated autoantibodies (GAD65, IA-2, ZnT8) were determined for forty children in a cross-sectional approach. Patients were divided into vitamin D-deficient, -insufficient and -sufficient subgroup, and their correlations between ALP or immune parameters were analyzed using correlation and regression analysis. The findings revealed that 42% of patients were deficient, 30% insufficient and 28% sufficient in vitamin D. Deficiency in vitamin D was linked to higher levels of ALP and more frequent autoantibody positivity. Serious inverse relationships were found between 25(OH) D and ALP, whereas immunoglobulin correlated to a moderate degree with vitamin D. These results indicate that the vitamin D deficiency observed in young children with T1DM may be associated with altered bone metabolism and increased autoimmunity. Serial testing for vitamin D and ALP may be a useful market in metabolic and immune changes in children with T1DM. Further longitudinal studies are warranted.